Squrt(4x-3)=squrt(9+x)

Simple and best practice solution for Squrt(4x-3)=squrt(9+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Squrt(4x-3)=squrt(9+x) equation:


Simplifying
Squrt(4x + -3) = squrt(9 + x)

Reorder the terms:
qrtuS(-3 + 4x) = squrt(9 + x)
(-3 * qrtuS + 4x * qrtuS) = squrt(9 + x)
(-3qrtuS + 4qrtuxS) = squrt(9 + x)
-3qrtuS + 4qrtuxS = (9 * qrstu + x * qrstu)
-3qrtuS + 4qrtuxS = (9qrstu + qrstux)

Solving
-3qrtuS + 4qrtuxS = 9qrstu + qrstux

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-9qrstu' to each side of the equation.
-3qrtuS + -9qrstu + 4qrtuxS = 9qrstu + -9qrstu + qrstux

Reorder the terms:
-9qrstu + -3qrtuS + 4qrtuxS = 9qrstu + -9qrstu + qrstux

Combine like terms: 9qrstu + -9qrstu = 0
-9qrstu + -3qrtuS + 4qrtuxS = 0 + qrstux
-9qrstu + -3qrtuS + 4qrtuxS = qrstux

Add '-1qrstux' to each side of the equation.
-9qrstu + -3qrtuS + -1qrstux + 4qrtuxS = qrstux + -1qrstux

Reorder the terms:
-9qrstu + -1qrstux + -3qrtuS + 4qrtuxS = qrstux + -1qrstux

Combine like terms: qrstux + -1qrstux = 0
-9qrstu + -1qrstux + -3qrtuS + 4qrtuxS = 0

Factor out the Greatest Common Factor (GCF), 'qrtu'.
qrtu(-9s + -1sx + -3S + 4xS) = 0

Subproblem 1

Set the factor 'qrtu' equal to zero and attempt to solve: Simplifying qrtu = 0 Solving qrtu = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrtu = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-9s + -1sx + -3S + 4xS)' equal to zero and attempt to solve: Simplifying -9s + -1sx + -3S + 4xS = 0 Reorder the terms: -3S + -9s + -1sx + 4xS = 0 Solving -3S + -9s + -1sx + 4xS = 0 Move all terms containing q to the left, all other terms to the right. Add '3S' to each side of the equation. -3S + -9s + -1sx + 3S + 4xS = 0 + 3S Reorder the terms: -3S + 3S + -9s + -1sx + 4xS = 0 + 3S Combine like terms: -3S + 3S = 0 0 + -9s + -1sx + 4xS = 0 + 3S -9s + -1sx + 4xS = 0 + 3S Remove the zero: -9s + -1sx + 4xS = 3S Add '9s' to each side of the equation. -9s + -1sx + 9s + 4xS = 3S + 9s Reorder the terms: -9s + 9s + -1sx + 4xS = 3S + 9s Combine like terms: -9s + 9s = 0 0 + -1sx + 4xS = 3S + 9s -1sx + 4xS = 3S + 9s Add 'sx' to each side of the equation. -1sx + sx + 4xS = 3S + 9s + sx Combine like terms: -1sx + sx = 0 0 + 4xS = 3S + 9s + sx 4xS = 3S + 9s + sx Add '-4xS' to each side of the equation. 4xS + -4xS = 3S + 9s + sx + -4xS Combine like terms: 4xS + -4xS = 0 0 = 3S + 9s + sx + -4xS Simplifying 0 = 3S + 9s + sx + -4xS The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| S-3=2s+6 | | 2+p=77 | | 40a^2+19a-3= | | 6(u-85)=66 | | 8(t+2)=56 | | 7=2s-11 | | 4n-10=2 | | 10-3r=4 | | 4c+9y=72 | | (10x)-6=24 | | -7x+2=x-14 | | Y=268 | | ln(4-2x)=0 | | Y=256+12 | | 9+3x=-6x+63 | | Y=(32)+12 | | -4x+10=-2x-14 | | 2x+1=-3x+41 | | 20x=9y-15 | | 9+2x=x+14 | | -6+3x=-2x-56 | | 6x+35+8x-23+y+88+3y=180 | | 4-7x=-5x-16 | | 12=y^2+4y | | 6x^2+x-12=468 | | 4x+20+x+5+30=180 | | 9(9+-4)=12(12t-3) | | 6x+x-12=468 | | 4y-12=y^2 | | (2x-1)(5x+1)= | | 3x-15+6x+8=15 | | 3x^2+2x^2=117 |

Equations solver categories